Drug evaluation is also a clinical activity - Eduardo López-Briz; Mª Dolores Fraga-Fuentes; Ana Clopés-Estela; Ana Ortega-Eslava; Emilio Jesús Alegre-del Rey (Farmacia Hospitalaria)
The addition of a fourth year to the hospital pharmacy residency program has allowed trainees to rotate through various inpatient clinical units where they can, under the supervision of a specialist pharmacist, work shoulder to shoulder with other healthcare providers to ensure that patients receive the care they need. In addition to sharing their pharmacotherapeutic and pharmacokinetic knowledge (among others) with their colleagues, hospital pharmacists can and should contribute with their expertise in the areas of drug evaluation, selection and positioning. As no other healthcare professional masters like a pharmacist the intricacies of treatment efficacy or effectiveness, or of therapeutic safety, conveying this knowledge is yet another of the many clinical activities a hospital pharmacist must perform as a member of a multidisciplinary team, while assisting fellow-team members in deciding what medications are best suited to each patient. Both the public authorities and the pharmaceutical profession as a whole should make sure the pharmacist’s role is rightfully valued and given the recognition it deserves.